KETENTUAN PERKAWINAN DALAM KHI DAN IMPLIKASINYA BAGI FIQH MU’ASYARAH: Sebuah Analisis Gender - Sumbulah, Umi (EGALITA, 2007)
Compilation of Islamic laws (KHI) consists of some gender bias points such as point of Wali, Saksi, Nusyuz, Polygamy as well as wife-husband’s right and obligation.  It is not only causing various religious understanding which are bias but also to the marriage practice and to the asymmetrical pattern of relation. Those, further, may result in gender inequality problems of which women (mostly wives) and children are the most vulnerable group to experience the problems although men may experience that such kind of problems. Fiqh as the product of Ulama’s interpretation and judgment toward normative doctrines (Qur’an and Hadith) are influenced by socio-cultural and political setting under patriarchal social system. Nurture theory on women and men’ social role contributes also to the marginalization and sub-ordination toward women in husband-wife relation in the family. Then, Counter Legal Draft (CLD) that is compiled by gender mainstreaming working group of Ministry of Religious Affairs (DEPAG) is an alternative Marital Laws formula which are more considering women and marginalized minority group.